2022
DOI: 10.1186/s12955-022-02062-1
|View full text |Cite
|
Sign up to set email alerts
|

Convergent validity of EQ-5D with core outcomes in dementia: a systematic review

Abstract: Objectives To explore through a systematic review, the convergent validity of EQ-5D (EQ-5D-3L and EQ-5D-5L (total score and dimensions)) with core outcomes in dementia and investigate how this may be impacted by rater-type; with the aim of informing researchers when choosing measures to use in dementia trials. Methods To identify articles relevant to the convergent validity of EQ-5D with core dementia outcomes, three databases were electronically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…Though the descriptive system and VAS assess distinct health constructs, we found the two components had medium correlation with each other, and showed similarities regarding the significant associations with total and sub‐scores of MBI‐C. Our results were in accordance with previous studies showing correlations of EQ‐5D dimensions and global cognition, ADL, and NPS in dementia 40 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Though the descriptive system and VAS assess distinct health constructs, we found the two components had medium correlation with each other, and showed similarities regarding the significant associations with total and sub‐scores of MBI‐C. Our results were in accordance with previous studies showing correlations of EQ‐5D dimensions and global cognition, ADL, and NPS in dementia 40 …”
Section: Discussionsupporting
confidence: 90%
“…Though the descriptive system and VAS assess distinct health constructs, we found the two components had medium correlation with each other, and showed similarities regarding the significant associations with total and sub-scores of MBI-C. Our results were in accordance with previous studies showing correlations of EQ-5D dimensions and global cognition, ADL, and NPS in dementia. 40 The general manifestation of NPS has been reported to impair PWDs' self-rated HR-QoL in PWDs and people with MCI, but only a few studies have comprehensively examined NPS in MCI 11,12 ; few studies have specifically investigated the influence of certain NPS aspects on QoL in older adults without dementia. We found that people with MBI had more severe NPS in all MBI-C subdomains and lower HR-QoL in EQ-5D than older adults without MBI.…”
Section: Quality Of Life (Eq-5d Index) Quality Of Life (Eq-5d Vas)mentioning
confidence: 99%